American Animals in Pehr Kalm’s Travels Publication: Experience, Animal Behavior and Interactivity (1749-1755) - Capozzi, Rebeca (Historia Ambiental Latinoamericana y Caribeña (HALAC) revista de la Solcha, 2026)
This article analyses Pehr Kalm’s (1716–1779) observations of American wildlife, as recorded during his travels to North America between 1748 and 1751. Alongside the naturalist John Reinhold Forster (1729–1798), Kalm published his observations of American flora and fauna in a work entitled Travels into North America, Containing Its Natural History, and a Circumstantial Account of Its Plantations and Agriculture in General, With the Civil, Ecclesiastical, and Commercial State of the Country, and the Manners of the Inhabitants. This was published in two volumes in London in 1772. Through qualitative analysis of Kalm’s texts, descriptions and correspondence with Linnaeus, as well as some of Forster’s manuscripts, this article aims to understand the significance of animal interactions in the development of new areas of study for naturalists interested in advancing agriculture and studying natural economies in America. To this end, I engage with Ewa Domanska’s (2010) concept of ’disobedient objects’ and Chris Pearson’s (2015) discussion of animal resistance throughout history. Through this article, I demonstrate how first-hand experience shaped a more detailed understanding of the relationship between animals and their habitats.